Numerical Analysis of the Influence of Foundation Pit Excavation on the Deformation of an Existing Tunnel - Shuai, Lan; Lin, Daishu (Journal of Progress in Civil Engineering, 2025)
In this paper, taking a new hotel project near the existing tunnel as an example, the deformation effect of the existing tunnel during the excavation process is simulated by using the MIDAS GTS NX numerical simulation finite element software, and it is concluded that the excavation and unloading of the foundation pit will cause the vertical settlement displacement and horizontal displacement of the tunnel. Among them, the maximum vertical settlement displacement is 0.47mm, and the maximum horizontal displacement is 0.41mm, which are in line with the local control and early warning values, and the entire foundation pit excavation process is within a safe and controllable range.